2021
DOI: 10.1371/journal.pone.0238087
|View full text |Cite
|
Sign up to set email alerts
|

The historical range and drivers of decline of the Tapanuli orangutan

Abstract: The Tapanuli Orangutan (Pongo tapanuliensis) is the most threatened great ape species in the world. It is restricted to an area of about 1,000 km2 of upland forest where fewer than 800 animals survive in three declining subpopulations. Through a historical ecology approach involving analysis of newspaper, journals, books and museum records from the early 1800s to 2009, we demonstrate that historically Pongo tapanuliensis inhabited a much larger area, and occurred across a much wider range of habitat types and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…• Pathogen risk mitigation strategies do not appear to be consistently applied; lack of crowd control at rescue and release events, lack of PPE use, and limited pathogen surveillance pose notable risks of pathogen transfer to rehabilitant and wild populations • Orangutans are Critically Endangered. Deforestation, habitat fragmentation and killing are most pressing needs • Translocation is often viewed as the preferred solution despite higher cost and risks • Diverse stakeholder needs • Wicked complexity of orangutan conservation issues (5), (9,10), (39), (40,41), (42) What are the management goals and decisions needed? How will the risk analysis help?…”
Section: Question Summary Description Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…• Pathogen risk mitigation strategies do not appear to be consistently applied; lack of crowd control at rescue and release events, lack of PPE use, and limited pathogen surveillance pose notable risks of pathogen transfer to rehabilitant and wild populations • Orangutans are Critically Endangered. Deforestation, habitat fragmentation and killing are most pressing needs • Translocation is often viewed as the preferred solution despite higher cost and risks • Diverse stakeholder needs • Wicked complexity of orangutan conservation issues (5), (9,10), (39), (40,41), (42) What are the management goals and decisions needed? How will the risk analysis help?…”
Section: Question Summary Description Referencesmentioning
confidence: 99%
“…Orangutan metapopulations are at risk from these same factors and may be harmed by removal of animals by wild-to-wild translocation. In areas of orangutan distribution where habitats have been degraded, fragmented or deforested, ecosystem functions are likely also compromised ( 5), (40,41), ( 43), (42) Are there any policy or regulation considerations?…”
Section: Question Summary Description Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, Tapanuli orangutans were found from the upland of West Toba lake in North Sumatra to the Bukit Tinggi district, West Sumatra (Meijaard et al, 2021). The current population was found within the Batang Toru ecosystem, North Sumatera.…”
Section: Study Areamentioning
confidence: 99%
“…Those potential natural corridors shall be protected, and an artificial corridor could be added to facilitate orangutans' movement, specifically among the small forest patches (Ancrenaz et al, 2021). It was analyzed that one of the causes of the declining orangutans' population is hunting (Meijaard et al, 2011;Meijaard et al, 2012;Davis et al, 2013;Abram et al, 2015;Voigt et al, 2018;Meijaard et al, 2021). Moreover, Wich et al (2012) observed that hunting for Sumatran orangutan often occurred within lower geographical elevation.…”
Section: Management Implicationsmentioning
confidence: 99%